Managing biotic interactions for ecological intensification of agroecosystems - Gaba, Sabrina; Bretagnolle, François; Rigaud, Thierry; Philippot, Laurent (Frontiers in Ecology and Evolution, 2014)
Agriculture faces the challenge of increasing food production while simultaneously reducing the use of inputs and delivering other ecosystem services. Ecological intensification of agriculture is a paradigm shift, which has recently been proposed to meet such challenges through the manipulation of biotic interactions. While this approach opens up new possibilities, there are many constraints related to the complexity of agroecosystems that make it difficult to implement. Future advances, which are essential to guide agricultural policy, require an eco-evolutionary framework to ensure that ecological intensification is beneficial in the long term.